Identities, Borders, Orders : Rethinking International Relations Theory - Lapid, Yosef, 1947-; Jacobson, David, 1959-; Albert, Mathias (Book collections on Project MUSE., 2001)
Informed by current debates in social theory, these contributors take up a variety of substantive, theoretical, and normative issues such as migration, nationalism, citizenship, human rights, democracy, and security.